A qualitative method for analysing multivoicedness. (December 2015) - Aveling, Emma-Louise; Gillespie, Alex; Cornish, Flora
'Multivoicedness' and the 'multivoiced Self' have become important theoretical concepts guiding research. Drawing on the tradition of dialogism, the Self is conceptualised as being constituted by a multiplicity of dynamic, interacting voices. Despite the growth in literature and empirical research, there remains a paucity of established methodological tools for analysing the multivoiced Self using qualitative data. In this article, we set out a systematic, practical 'how-to' guide for analysing multivoicedness. Using theoretically derived tools, our three-step method comprises: identifying the voices of I-positions within the Self's talk (or text), identifying the voices of 'inner-Others', and examining the dialogue and relationships between the different voices. We elaborate each step and illustrate our method using examples from a published paper in which data were analysed using this method. We conclude by offering more general principles for the use of the method and discussing potential applications.